Adekwatność systemu budżetowego przedsiębiorstwa do wymagań wynikających z oceny utraty wartości jego aktywów - Karmańska, Anna (Adequateness of Budget System of an Enterprise to Demands Resulted From Impairment of Assets Valuation, 2007)
Methods of impairment of assets valuation are tightly connected with budget system of an enterprise. Reliable balance sheet valuation of assets presented in financial statement and liabilities of an enterprise are the conditions of usefulness of information generated by financial accounting system. Therefore, budget system in an enterprise must fulfill some demands in accordance with accounting standards. The aim of this paper is an analysis of quality criteria which budget system of an enterprise must correspond to and thanks to which it would be possible to accept by accounting standards estimated and - important on this field - values crucial for valuation of assets, which an enterprise posses and which determine its business. The article presents one of many fields where more and more the integration of managerial accounting tools, budgeting and controlling together with financial accounting system are visible, mirroring achievements and economical potential of an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 78-100